Risk factors of foot ulceration in patients with Diabetes Mellitus type 2 - Patricia Bañuelos-Barrera; Elva Dolores Arias-Merino; Yolanda Banuelos-Barrera (Universidad de Antioquia, 2013)
Objective. Identify the risk factors for foot ulceration in patients with diabetes type 2 (DM2) who attended a primary care center in the city of Colima (Mexico). Methodology. This was a descriptive cross-sectional study conducted during 2012 with the participation of 87 patients with DM2 from both sexes and older than 30 years of age. Socio-demographic, anthropometric, clinical, and biochemical variables were measured. The study inquired about prior evaluation of the feet and prior education on diabetes by the healthcare team. Results. The mean age was 59 years and 70% were women. The average number of years since diagnosis was nine years; only 35% had good glycemia control; 66% engage in exercise; 51% wear open shoes; none had temperature differences in the feet; 82% had some type of dermatological abnormality; 50% had deformities in their feet. A total of 24% had been diagnosed with peripheral neuropathy and another 11% had peripheral vascular disease. Sixty percent of all the patients had risk of foot ulceration. Only 23% of the participants had had previous foot exams. One of every three diabetic patients had received education about the disease. Conclusion. An important proportion of the patients had risk of foot ulceration, contrary to the insufficient percentage of individuals with previous inspection and education about foot care. For nursing, it is an area of opportunity in this level of care to improve the inspection and education on diabetes, specifically on foot care, mainly in those patients with a prolonged evolution of the disease, deficient glycemia control, and risk of ulceration.